Acupuncture modulates the AMPK/PGC-1 signaling pathway to facilitate mitochondrial biogenesis and neural recovery in ischemic stroke rats - Guo, Kaixin; Lu, Yan (Frontiers in Molecular Neuroscience, 2024)
Aims The main objective of this study was to investigate the role and mechanism of acupuncture on anti-nerve injury in the acute phase by regulating mitochondrial energy metabolism via monophosphate-activated protein kinase (AMPK)/peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) axis in rat ischemic stroke. Main methods Middle cerebral artery occlusion (MCAO) was established by middle cerebral artery occlusion/reperfusion. One-week of acupuncture was performed during the acute phase of ischemic stroke. The neurological function and brain tissue integrity were evaluated. Mitochondrial function (intracellular ATP level and the activity of mitochondrial respiratory chain complex I) and the level of NADH oxidase (NOX) were detected by enzymatic chemistry. Next, the potential molecular mechanisms were explored by western blotting, fluorescence quantitative PCR and immunohistochemistry method. Key findings (1) Acupuncture treatment for MCAO/R rats showed a significant improvement in the infarcted tissue accompanied by functional recovery in Zea-Longa score and balance beam score outcomes, motor function performances. (2) Acupuncture increased the levels of ATP and mitochondrial respiratory chain complex I, decreased the NOX levels in cerebral ischemia established by suture-occluded method. (3) Acupuncture reduced the necrosis dissolution of neuronal cells and meningeal edema, while promoting angiogenesis. (4) Quantitative immunohistochemical staining results showed acupuncture can increase the expression of AMPK, p-AMPK and the mitochondrial transcription factor PGC-1α, NRF2, TFAM and uncoupling protein 2 (UCP2). Meanwhile, acupuncture treatment up-regulated the expression of the corresponding protein. (5) Subsequently, acupuncture enhanced AMPK phosphorylation as well as the expression of PGC-1α, NRF2, TFAM and UCP2, implicated in mitochondrial synthesis and cellular apoptosis. (6) Finally, injections of AMPK antagonists and activators confirmed AMPK as a therapeutic target for the anti-nerve damage effects of acupuncture. Significance Acupuncture intervention relieved ischemic stroke progression in MCAO rats by promoting energy metabolism and mitochondrial biogenesis in the brain and alleviating neuronal apoptosis, which was mediated by eliciting AMPK/PGC-1α axis, among them AMPK is a therapeutic target.